Design and in vitro evaluation of chlorpheniramine maleate from different eudragit based matrix patches: Effect of platicizer and chemical enhancers - Rajan, R; Sheba Rani, N.D.; Kajal, G.; Sanjoy Kumar, D; Jasmina, K; Arunabha, N (Ars Pharmaceutica (Internet), 2009)
The release and permeation studies were carried out for developing transdermal therapeutic systems with chlorpheniramine maleate (CPM). The patches were prepared with eudragit RS-100 and RL-100 with/without polyvinyl pyrrolidone (PVP) and dibutyl phthalate (DBP) in different compositions. Thickness, tensile strength, drug content, moisture content and water absorption studies of the patches were measured. In vitro release/permeation of CPM was studied in modified Keshary-Chien diffusion cell. Chemical enhancers like l-menthol, oleic acid and phospholipon80 were added to compare the release pattern of the drug. The percent release of the drug from matrix patch increased with increase of PVP & DBP but the tensile strength decreased with the increase of DBP & PVP. Experimental release/permeation data of different formulations of the matrix systems are reported. Also the drug-polymer interaction was investigated by ATR-FTIR studies. The discussion was correlated the efficient matrix dispersion patch from suitable eudragit polymers for transdermal antihistamine applications in film device industry.